Knowing Is Not Enough: A Mixed-Methods Study of Antimicrobial Resistance Knowledge, Attitudes, and Practises Among Maasai Pastoralists - Mangesho, Peter E.; Caudell, Mark A.; Mwakapeje, Elibariki R.; Ole-Neselle, Moses; Kimani, Tabitha; Dorado-García, Alejandro; Kabali, Emmanuel; Fasina, Folorunso O. (Frontiers in Veterinary Science, 2021)
Global, national, and local efforts to limit antimicrobial resistance (AMR) often stress the importance of raising awareness among users, sellers, and prescribers of antimicrobial drugs. This emphasis is founded upon two assumptions. First, awareness is limited, particularly concerning the links between antimicrobial use (AMU) and AMR. Second, “filling the awareness gaps” will motivate practises that will limit AMR. The first assumption is supported by knowledge, attitudes, and practises (KAP) surveys but these same studies provide mixed support for the second, with several studies finding that knowledge and attitudes are not correlated with related practises. This disconnect may arise as these surveys typically do not collect data on the cultural or historical contexts that pattern AMU. To explore how these contexts impact KAP related to AMU and AMR, we use a mixed-methods approach to examine veterinary practises among Maasai pastoralists in Tanzania. We combine a quantitative KAP survey (N = 195 households) with extensive qualitative data from focus group discussions (N = 55 participants). Results document limited awareness of AMR but also find that knowledge and attitudes are not correlated with practise. Thematic analysis of qualitative data pointed to three reasons behind this disconnect, including (1) Maasai self-perceptions as veterinary experts, (2) the central role of livestock in Maasai culture, and (3) the use of ethnoveterinary knowledge in animal health treatment. We argue that mixed-method approaches will be critical to developing the targeted awareness campaigns needed to limit the emergence and transmission of AMR.